Analysis and optimal design of microstrip sensors - Khalid, K.B.; Maclean, T.S.M.; Razaz, M.; Webb, P.W. (Institution of Engineering and Technology (IET), 1988)
The analysis and optimal design of a microstrip sensor for measuring the water content of rubber latex is described. The microstrip structure consists of three layers: substrate, protective layer and semi-infinite layer of wet medium. A functional relationship has been developed between the attenuation and the water content of the latex, and close agreement has been found between the computed and experimental results. A computer program has also been developed which optimizes the sensitivity for a given water content.